Antike Grabbauten in Noricum Katalog und Auswertung von Werkstücken als Beitrag zur Rekonstruktion und Typologie - Kremer, Gabrielle (Österreichisches Archäologisches Institut, 2001)
Most of the stone blocks left from roman time in the province of Noricum were initially part of funerary monuments. The aim of this book is to reconstruct the architectural form of these monumental tombs, to develope a typological classification and to draw conclusions concerning the history and the arts of the province. The shape of the blocks and the technical details to observe on the surfaces at the same time as the structure and the representations of the reliefs give us informations about the function of these blocks in an architectural context. By comparison to the well preserved monuments of Sempeter - whose reconstruction is critically reviewed - and to funerary monuments of Italy and other roman provinces, it is possible to propose a reconstruction of numerous monuments in Noricum. A classification of excavated funeral sites including workpieces of stone provides further information. Thus a survey of the different types of funerary monuments existing in roman Noricum is given and most of the recorded stone blocks may be typologically classified. A total of 227 workpieces or groups of workpieces are collected in catalogue L classified as parts of the monument types 'ae&cu1a', 'canopy', 'altar', 'pile', 'masonry construction', 'tumulus' or 'enclosure'. For some of them a theoretical reconstruction is proposed and they are mostly represented by drawings or photographs. The 414 pieces in catalogue 11 may not be determined typologically, but nevertheless allow a discussion of their initial architectural function. Catalogue III includes the evidence of 44 excavated monuments. The analysis of the presented material shows the chronological and regional evolution of the different types of funerary monuments. The evidence given by the inscriptions, the portraits and the reliefs allows to examine the correlation which is possibly existing between the type of monument chosen and the social position of its owner. Finally the geographical spreading and the variabel frequency of the different types in Noricum is shown and discussed. In appendix I some relevant measurements and proportions of architectural elements are listed- Appendix H gives a survey of the monuments with are typologically classified and whose owners are known at least partly.